Litsea dorsalicana (Lauraceae): a new species from limestone areas in northern Guangxi, China - Han, Meng-Qi; Huang, Yu-Song; Liu, Jing; Xu, Wei-Bin (Phytotaxa, 2013)
Litsea dorsalicana, a new species of Lauraceae from northern Guangxi, China is described and illustrated. It is similar to Litsea elongata, but can be distinguished from the latter by twigs, buds and abaxial leaf surface densely covered with gray-white pubescence, leaf blade oblanceolate to oblong, to 29.5 cm long, 10.5 cm wide, base cuneate to attenuate, fruit red, cupule cup-shaped, once or twice cleft at the margin.